Kurban atau Korban : Teologi Persembahan dari Selebrasi ke Aksi - Rachman, Rasid (Theologia in Loco, 2025)
Questioning the liturgy of the offering, which has been solemnly carried out but has become so common as a fundraiser for the church, is the starting point of revitalizing this discourse through research. Etymological study, liturgical study, biblical study, and customs, are tools to debunk the hypothesis that sacrifices and sacrifices have their own meanings, so that offerings do not stop only at the delivery of materials and properties at the banquet table. Andrea Bieler and Luise Schottroff, The Eucharist: Bodies, Bread, and Resurrection, inspired the theology of offerings in three forms, namely: vicarious offering and symbolic offering at the altar, and a reasonable offering as offering exchange in a real forms for outside of the church. Sending a gift as an offering of gratitude to God is a returning of gifts to other people and the earth.